The problems of recovery and development of thermal power engineering at the controlled territories of Donetsk and Lugansk regions - Snihova, O. (Економічний вісник Донбасу, 2017)
The assessment of representation of thermal power plants at the controlled territories of Donetsk and Lugansk regions has been done. The opportunities and prospects of thermal power engineering recovery has been estimated in the new economic and political conditions, characterized by the loss of a part of Eastern regions’ potential. Weaknesses and limitations of the sector functioning in the new conditions have been revealed. Risks (threats) that can impede, complicate or disable its development, have been determined.